Pulmonary embolism. A case report - Pedro J. Barrios Fuentes; Felix Silvino Molina Díaz; Indira Martínez Chavarría (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
The case of a male, white skin, 38 years old patient who came to the emergency department because of a severe respiratory distress is reported. The left patella fracture history was collected and an immobilization cast was implemented. The posterior to anterior chest X-ray showed opacities in the form of a veil at the base of the left hemithorax as well as increased cardiothoracic rates. A lung computed tomography angiography scan was performed using a SIEMENS SESATION 64 multislice computed tomography scanner. The study was rebuilt using volume rendering technique and 3D applications with virtual angioscopy. Thrombus occlusion was evident at the trunk of the left pulmonary artery and its branches. The patient was admitted for anticoagulation treatment. Patients with patellar fracture as a trigger for this serious condition involving life-risk had not been treated in this hospital, that is why it was decided to publish this case, as well as for the implementation of such an innovative, useful and quick diagnosis aided by multislice computed tomography angiography.